Fifty shades of QE: Conflicts of interest in economic research - Brian Fabo; Martina Jančoková; Elisabeth Kempf; Luboš Pástor (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2021)
Central banks sometimes evaluate their own policies. To assess the inherent conflict of interest, we compare the research findings of central bank researchers and academic economists regarding the macroeconomic effects of quantitative easing (QE). We find that central bank papers report larger effects of QE on output and inflation. Central bankers are also more likely to report significant effects of QE on output and to use more positive language in the abstract. Central bankers who report larger QE effects on output experience more favorable career outcomes. A survey of central banks reveals substantial involvement of bank management in research production.
urn:nbn:de:hebis:30:3-564449
Keywords: A11; E52; E58; G28; 330